Pengambilan Keputusan Masyarakat Banjar Dalam Pengobatan Ba’urut Pada Patah Tulang - RACHMAN, AULIA; Oktovin, Oktovin; Unja, Ermeisi Er (STIKES Suaka Insan, 2023)
South Kalimantan Province, 2018 Riskesdes data showed that several types of injuries were experienced, including fractures at 4.2 percent, leading to permanent physical disability at 7.2 percent, and the traditional tool-less treatment, ba'ur, was the first choice. This research is a qualitative study with a phenomenological research design with a population of people who experience choosing traditional Ba'urut treatment. This research looks at phenomenology to explore what are the decision-making factors in the community. The samples used in this study are participants with a history of traditional Ba'urut treatment with closed fractures, willing to become participants, participants with adult age restrictions, who communicate well, Ba'urut history is not more than 3 years, domiciled in South Kalimantan. Keywords: Ba’urut; Banjar; Decision Making; Fractur; Traditional Medicine